Faktor-Faktor yang Mempengaruhi Tax Avoidance pada Perusahaan Manufaktur - Greta Graheni Wisnu; Yuniarwati (Syntax Literate, 2023)
The objective of this study is to obtain empirical evidence about the effect of transfer pricing, profitability, and foreign ownership on tax avoidance in manufacturing companies which listed on Indonesian Stock Exchange for period 2019-2021. The samples on this study were collected using purposive sampling method and obtained samples of 54 manufacturing companies that met the predetermined criteria. The results of the study show that transfer pricing and profitability have no significant effect on tax avoidance. While foreign ownership has a significant effect on tax avoidance.